Dynamic of negative ions in potassium-D-ribose collisions - Almeida, D. (2018)
D.A. and F. F. S. acknowledge the Portuguese Foundation for Science and Technology (FCT-MEC) for a post-graduate Grant No. SFRH/BD/61645/2009 and post-doctoral Grant No. SFRH/BPD/68979/2010, respectively. We are also grateful to the partial funding from the Portuguese research Grant Nos. PEst-OE/FIS/UI0068/2011 and PTDC/FIS-ATO/1832/2012 through FCT-MEC. P.L.-V. acknowledges his visiting professor position at The Open University, UK. The Spanish Ministerio de Economia y Competitividad (Project No. FIS 2012-31230) is also acknowledged. Some of this work forms part of the EU/ESF COST Actions Nano-IBCT-MP1002 and The Chemical Cosmos-CM0805.